Observations Worth versus Action Learning: The Role of Site Visit in Learning - Anwar, Faisal (Hamdan Bin Mohammed e-University, 2012)
This paper demonstrates the role of site visit in learning hydraulics in a 4th year undergraduate Civil Engineering unit (optional unit, prerequisite-pump and open channel hydraulics) at Curtin University, Western Australia through the process of action learning. The unit is divided into lectures and a site visit. Victoria Dam site in Western Australia was chosen for this purpose because the site is a combination of different structures taught in the lectures and closer to Curtin. Three guides from Water Corporation (owner of the dam) explained different aspects of dam to the students. In a week after the visit, the students sat for a test on the field trip where they were asked to answer 8 questions. An anonymous questionnaire survey was conducted immediately after the test where they were asked to put their level of agreement with statements about (i) their motivation and learning hydraulic engineering from the site visit (ii) overall learning outcome from the site visit, (ii) assessment of learning hydraulic engineering from site visit (iii) coordination of the site visit and (iv) their overall satisfaction. The results revealed that the overall satisfaction of learning hydraulic engineering from site visit was 80%. The average agreement for all the items was found 72%. The most agreements (79-88%) were found for their motivation and learning process of hydraulic engineering from the site visit. The least agreement (42%) was found for the method of assessment for site visit but their assessment test results shows that more than 62% of the students could obtain >70% marks with an average marks of 74%. The results also revealed that the action learning from site visit helps student to develop their self-confidence and readiness to take responsibility and initiative for any engineering development.